First Principles: Gabriele Stornaloco and Milan Cathedral. (19th October 2016) - Sebregondi, Giulia Ceriani; Schofield, Richard
Abstract: The construction from 1386 of Milan Cathedral, the largest Gothic church ever constructed in Italy, was one of the most important episodes in the history of Italian and European architecture. The documentation of the late Trecento and early Quattrocento discussions over how to build the Cathedral is extraordinarily rich and extensive, and permits a consideration of the project from many points of view including the relationship between medieval architectural theory and an actual project. At the same time, any enquiry has to contend with the copious modern literature and the conclusions that have been reached hitherto – often erroneously in our view – about many of the most salient points. We thus re-examine published and unpublished documentation and the existing literature, analysing especially the format of the building's elevation, the proposals by Gabriele Stornaloco and Jean Mignot, and the drawings attributed to Antonio di Vincenzo. We also reconsider the notions of ars and scientia which have previously been misinterpreted in discussions of the cathedral documentation.